A note on KiwiSaver and migrants on temporary visas. Issue 1 (2nd January 2023) - Meehan, Lisa; Mitchell, Livvy; Pacheco, Gail
Abstract : New Zealand's (NZ) current policy setting excludes migrants on work or student temporary visas from joining KiwiSaver (KS). Migrants on temporary visas, therefore, cannot access a savings vehicle that makes saving for retirement convenient and provides financial incentives to save. This research note estimates the extent of this migrant KS ineligibility issue. We use linked administrative data to create a cohort of 70, 000 NZ migrants on temporary work or student visas in 2009 and follow them for ten years. Results show that after five years, over half of the cohort live overseas and about 10, 000 remain on temporary visas and hence are still ineligible for KS. Using KS enrolment of a comparison group of resident-class migrants over the same time period, we estimate that just over half of employed temporary migrants might have potentially joined KS if eligible. The lost individual KS contributions range between $36, 000 and $51, 000 by time the migrant reaches 65 years old. Our findings contribute to the policy debate of whether the eligibility criteria of NZ's KS scheme should be revised to allow temporary visa holders to join.